Can usage be used for scholars' evaluation in the construction of smart libraries?. Issue 1 (4th March 2020) - Liu, Yunmei; Li, Changling; Gao, Zichun
Abstract : Purpose: With the development of Web2.0 and publishing digitalization, traditional libraries and evaluation citation system can no longer indicate academic paper influence validly. Therefore, it is necessary to construct smart library and find the evaluation effect of Internet metrics-Usage. Design/methodology/approach: This study puts forward four indexes of scholars' evaluation based on Usage (total Usage ( U ), average Usage rate ( U / N ), h u -index and p u -index), which refer to citation indexes, takes the 35 high-output scholars in the field of library and information science in the WoS database as examples, analyzes performance of different scholars evaluation indexes based on Usage and compares the differences and correlations between "citation indicators" and "usage indicators." Findings: This study results show that p u -index is the strongest index to evaluate scholars. Second, there is a high correlation and strong mechanism based on time dependence and interactions between Usage and citation. Third, compared to "citation indicators", the "usage indicators" has a larger numerical value and wider measurement range, which can break the time limitation of citation, and scientifically evaluate young scholars and newly published paper by scholars. Originality/value: This paper proposes the p u -index – a relatively superior mathematical model for Usage and provides reference for the scholars' evaluation policy of the smart library. This model can not only provide fair evaluation conditions for young scientists but also shorten the evaluation effect of the time lag of cited indicators. In addition, the "usage indicators" in this paper are new scientific evaluation indicators generated in the network environment. Applying it to the academic evaluation system will make the research papers widely accepted by the public and will also encourage scientists to follow the development of the Internet age and pursue research with equal emphasis on quantity and quality.